Citizenship, math and gender: Exploring immigrant students' choice of majors - Marina Murat (Global Labor Organization (GLO), 2024)
This paper investigates whether citizenship of immigrant students in the host country influences their choice of majors, and whether these effects differ by gender. Using detailed students' data from an Italian university, combined with characteristics of the countries of origin, I examine the effects of citizenship on enrolments in educational areas categorized by their mathematical content. Results indicate a decrease in the likelihood of enrolment in math-intensive fields among students who acquire citizenship, particularly among males, leading to a reduction in gender gaps. Moreover, gender gaps are smaller and show a more pronounced decrease with citizenship as gender inequality in countries increases. Results are corroborated by matching and instrumental variables strategies. These findings shed light on the existence of trade-offs between empowerment, as manifested through citizenship, and major choices.
Keywords: I23; I24; I25; J16; 330; Citizenship; immigrants; higher education; math; gender gaps; gender inequality